THE RELEVANCE OF INVOLVING INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE MODERN EDUCATIONAL PROCESS (Education in the 21st Century, 2023)
Since the outdated methods and means of teaching do not meet the current requirements of the modern occupation and are not subject to the trends of rapid development of scientific and technical progress, this encourages teachers to introduce innovative teaching methods and use and adapt these technologies to the educational process. This problem is especially acute in the formation of professional skills and abilities, since for their more effective assimilation, the educational process requires the use of a large number of visual materials and interactive tools, which in turn positively contribute to the improvement of the achievement of the educational goal. These aspects determine the relevance of the research topic.               The subject of the study is the process of involving information and communication technologies in the modern educational process. Within the framework of the conducted research, a number of aspects regarding the expediency and possibility of involving information and educational technologies in the educational process were revealed. The work reveals the essence of information and communication technologies, the relevance of their involvement in the educational process. The advantages and potential of information and communication technologies in the classroom, independent work of applicants, in the organization of continuous education throughout life are determined.
Keywords: information and communication technologies; training; education; benefits; continuous education; informatization of society